Texas Voices Speak out about High-Stakes Testing: Preservice Teachers, Teachers, and Students - Belinda Bustos Flores; Ellen Riojas Clark (Arizona State University, 2015)
Although teachers and students are directly impacted by high-stakes testing policy mandates, their opinion is often left out during the decision-making process. As future educators, preservice teachers are also affected by these mandates; thus far, their perspectives have also been ignored. Providing these stakeholders a forum in which they can speak about accountability testing allows others to hear their voices in this controversial issue. To achieve this goal, we employed a qualitative design. Data gathered consisted of observational journals and threaded e-journals. Data were critically analyzed and triangulated. Trustworthiness was further established using peer-review and member checking. Emerging patterns revealed that, across grade levels, preservice and inservice teachers see the overemphasis on high-stakes testing as being intrusive on their curricular and instructional decision-making. They note that instructional decisions are not being made in the students' best interests. Across grade levels, students' perceptions and their approach to tests differ. These voices challenge notions of whether high-stakes tests are valid measures of students' learning, ability, or potential, and whether test results should be used as an accountability measure.